Modal Analysis of Aero-spiral Bevel Gear with Considering Temperature Field Action - Wentao Yu; Shijun Liu; Wenbo Xu; Hongtao Huang; Feng Wang (Jixie chuandong, 2021)
For the aero-spiral bevel gears，the temperature of flank surface will be greatly increased in the high speed and heavy load conditions. It is necessary to consider the modal condition with the temperature field in designing early. Based on the traditional linear modal theory，the modal analysis model of aero-spiral bevel gears is established，what is considering the influence of rotational speed and temperature field on the stiffness. According to the model，the modal analysis of a driven gear of an aero-spiral bevel gear is carried out. The results show that the speed has a great influence on the stiffness of the gear，and which is not necessarily negative，and the uneven distribution of temperature field also affects the results of the modal analysis. The pitch diameter vibration mode is the main mode what is affected by the speed and temperature field.